Effects of almond on cardiometabolic outcomes in patients with type 2 diabetes: A systematic review and meta‐analysis of randomized controlled trials. (20th April 2022) - Moosavian, Seyedeh Parisa; Rahimlou, Mehran; Rezaei Kelishadi, Mahnaz; Moradi, Sajjad; Jalili, Cyrus
Abstract: An enhanced risk for cardiovascular disease (CVD) still exists even when T2DM patients have tight control on blood sugar. Thus, identification of treatment approaches that address CVD risk factors may be useful for patients beyond the blood sugar management. Although emerging evidence suggests that nuts consumption have beneficial effects on cardiometabolic health, the effects of almond intake in patients with type 2 diabetes are still controversial. Therefore, our objective was to investigate the effect of almond on cardiometabolic outcomes in patients with T2DM through a systematic review and meta‐analysis of available randomized controlled trials (RCTs). A systematic search was conducted in PubMed, Web of Science, Scopus, Embase, and Google Scholar to identify relevant RCTs up to March 2021. There was no language and time limitation. Weighted mean difference (WMD) was pooled using a random effects model. Heterogeneity, sensitivity analysis, and publication bias were reported using standard methods. Nine RCTs were included in the final analysis. Almond intake resulted in significant reduction in low‐density lipoprotein cholesterol (LDL‐C) (WMD: −5.28 mg/dL; 95% CI, −9.92, −0.64; p = .026) compared with the control group. This lowering effect of LDL‐C was robust in subgroups with almond consumption >50 g/day, and baseline LDL‐C level <130 mg/dL. However, the effect of almond on total cholesterol, triglycerides, high‐density lipoprotein cholesterol, fasting plasma glucose, insulin, hemoglobin A1c, body mass index, weight, body fat, systolic and diastolic blood pressure, and CRP was not significant compared with the control group. In summary, the current meta‐analysis indicated that almond consumption decreased LDL‐C, and had no favorable effect on other cardiometabolic outcomes in patients with T2DM. However, further high‐quality studies are needed to firmly establish the clinical efficacy of the almond.